2020
DOI: 10.3390/su12155889
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Justice in The Netherlands: Presence and Quality of Greenspace Differ by Socioeconomic Status of Neighbourhoods

Abstract: Making our cities more sustainable includes the need to make the transition a just one. This paper focuses on distributive justice with regard to greenspace in cities. Urbanisation and densification will likely result in less greenspace in urban residential areas, especially in deprived neighbourhoods. This is a threat to the aim of healthy and liveable cities, as greenspace has positive effects on human health and well-being. In this study, we show that in The Netherlands, neighbourhoods with a low socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 50 publications
(71 reference statements)
4
22
0
Order By: Relevance
“…In these districts the relative number of inhabitants receiving social welfare is also higher, as is the relative number of migrants living there. This supports our earlier statement about environmental injustice (see [17,18]). In most cities the percentage of vegetation in a garden is lower related to these two social cultural factors, except for Rotterdam, especially when looking at the districts of Delfshaven, Noord, Crooswijk and Charlois, with a relatively highly percentage of vegetation in the garden.…”
Section: Social-cultural Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…In these districts the relative number of inhabitants receiving social welfare is also higher, as is the relative number of migrants living there. This supports our earlier statement about environmental injustice (see [17,18]). In most cities the percentage of vegetation in a garden is lower related to these two social cultural factors, except for Rotterdam, especially when looking at the districts of Delfshaven, Noord, Crooswijk and Charlois, with a relatively highly percentage of vegetation in the garden.…”
Section: Social-cultural Factorssupporting
confidence: 92%
“…In regions with a higher socioeconomic status a greater cover of large mature gardens with higher biodiversity exists, combined with a larger area of public green space. People who live in more deprived neighbourhoods have less nearby biodiverse spaces, and therefore encounter fewer opportunities to connect with nature and gain benefits from urban biodiversity, which also touches upon the issue of environmental justice [17,18]. According to Hand et al [19] gardens are the most preferred spaces for children, since they do not often make use of the more biodiverse areas in their surrounding neighbourhoods.…”
Section: The Role Of Gardens In Cities For Wellbeingmentioning
confidence: 99%
“…This result was not surprising for several reasons. Socioeconomic status is known to be positively related to mental health [ 67 , 68 , 69 ], while the levels of neighborhood greenness may also differ depending on the socioeconomic factors [ 70 , 71 ]. In a previous study, we found that in Stockholm County, the direction of the association between area level greenness and socio-economy showed opposite trends, depending on the type of municipality in focus [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result was not surprising for several reasons. Socioeconomic status is known to be positively related to mental health (68)(69)(70), while the levels of neighbourhood greenness may also differ depending on the socioeconomic factors (71,72). In a previous study, we found that in Stockholm County the direction of the association between area level greenness and socio-economy show opposite trends, depending on the type of the municipality in focus (73).…”
Section: Discussionmentioning
confidence: 69%